A non-functional neoepitope specific CD8+ T-cell response induced by tumor derived antigen exposure in vivo. (4th March 2019) - Vormehr, Mathias; Reinhard, Katharina; Blatnik, Renata; Josef, Kathrin; Beck, Jan David; Salomon, Nadja; Suchan, Martin; Selmi, Abderraouf; Vascotto, Fulvia; Zerweck, Johannes; Wenschuh, Holger; Diken, Mustafa; et al.
ABSTRACT: Cancer-associated mutations, mostly single nucleotide variations, can act as neoepitopes and prime targets for effective anti-cancer T-cell immunity. T cells recognizing cancer mutations are critical for the clinical activity of immune checkpoint blockade (ICB) and they are potent vaccine antigens. High frequencies of mutation-specific T cells are rarely spontaneously induced. Hence, therapies that broaden the tumor specific T-cell response are of interest. Here, we analyzed neoepitope-specific CD8 + T-cell responses mounted either spontaneously or after immunotherapy regimens, which induce local tumor inflammation and cell death, in mice bearing tumors of the widely used colon carcinoma cell line CT26. A comprehensive immune reactivity screening of 2474 peptides covering 628 transcribed CT26 point mutations was conducted. All tested treatment regimens were found to induce a single significant CD8 + T-cell response against a non-synonymous D733A point mutation in the Smc3 gene. Surprisingly, even though Smc3 D733A turned out to be the immune-dominant neoepitope in CT26 tumor bearing mice, neither T cells specific for this neoepitope nor their T cell receptors (TCRs) were able to recognize or lyse tumor cells. Moreover, vaccination with the D733A neoepitope did not result in anti-tumoral activity despite induction of specific T cells. This is to our knowledge the first report that neoepitope specific CD8 + T cells primed by tumor-released antigen exposure in vivo can be functionally irrelevant.